Determinants of Planktonic Foraminifera Calcite Flux: Implications for the Prediction of Intra‐ and Inter‐Annual Pelagic Carbonate Budgets. Issue 9 (12th September 2021) - Kiss, P.; Jonkers, L.; Hudáčková, N.; Reuter, R. T.; Donner, B.; Fischer, G.; Kucera, M.
Abstract: Planktonic foraminifera precipitate calcite shells, which after the death of the organisms are exported to the seafloor. Globally, the resulting calcite flux constitutes up to half of the pelagic calcite flux. Given their importance for the marine calcite budget and for the carbonate counter pump, which counteracts the biological pump in terms of oceanic capacity for CO2 uptake, it is crucial to understand the mechanisms regulating the planktonic foraminifera calcite flux. In principle, variability in individual species calcite flux could be caused by changes in (a) shell flux, (b) shell size, and (c) calcification intensity. Where size and calcification intensity differ among species, variations can be caused by changes in species composition. To assess the importance of these factors in regulating the planktonic foraminifera calcite flux, we investigated two sediment trap time series from the Cape Blanc upwelling area. On intra‐annual timescales, 82% of the variability in the calcite flux can be explained by shell flux alone. Since the intra‐annual flux variability at the study site covers the global range of mean annual shell fluxes, our results indicate that a global prediction of steady‐state planktonic foraminifera calcite flux can be predicted by shell flux variability in combination with species‐specific average shell mass. However, our results show that on inter‐annual timescales, shell mass variability can be as important as shell flux variability. Therefore, this implies that in order to predict temporal changes in the planktonic foraminifera calcite flux variability in shell size and calcification intensity also require considered. Key Points: On intra‐annual timescales, shell flux is the best predictor of variability in planktonic foraminifera calcite flux On inter‐annual timescales, variable shell mass is also required to constrain the variability in planktonic foraminifera calcite flux